Manajemen Pengembangan Kurikulum di Sekolah MI Al-Istianah Sidoarjo - Rohmah, Ainur; Salma, Masyqi; Muttaqin, M. Irsyad; Amalia, Kaniati (ARZUSIN, 2024)
The educational process in learning activities or in the classroom can run smoothly, comfortably and interactively if it is based on a good basic program. Education can be carried out well if the curriculum is used as the main tool to support the teaching and learning process, one of the government's efforts to improve the quality of education through program innovation. Curriculum research is one of the factors and ways to facilitate the implementation of education to achieve the stated goals. The school curriculum is an important part of education because it regulates the entire educational process from planning to assessment. The program development process includes the steps necessary to develop a program; can also be understood as steps to create a program or improve an existing program. The method used in preparing this article is qualitative by collecting data using interview and observation techniques related to curriculum development management. As a result, you can understand the curriculum development process so you know the steps taken to develop the curriculum at Madrasah Ibtidaiyah Taman Sidoarjoand substantiated in the main text and should not exaggerate the main conclusions.